The effect of nitrogen fertilization on the incidence of olive fruit fly, olive leaf spot and olive anthracnose in two olive cultivars grown in rainfed conditions - Rodrigues, M.A. (2018)
Pests and diseases can cause significant loss of olive yield and/or justify control measures with pesticides which are harmful to the environment. Several agroecological variables, such as fertilization, can favour or limit the incidence of pests and diseases. However, in olive, few studies exist on the subject than can assist in the implementation of more sustainable phytosanitary measures. In this study the effect of nitrogen fertilization (0, 20, 40 and 120 kg N ha−1) on the incidence of olive fruit fly (Bactrocera oleae), olive leaf spot (Spilocaea oleaginea) and olive anthracnose (Colletotrichum gloeosporioides) was evaluated in two olive orchards of the cultivars ‘Cobrançosa’ and ‘Madural’. The study took place in 2017 and 2018 in Lombo, NE Portugal. Nitrogen fertilization significantly increased olive yield and nitrogen concentrations in plant tissues and induced a delay in fruit maturity. The incidence of the olive fruit fly was significantly lower in the more fertilized treatments of both cultivars. However, ‘Madural’ showed itself to be more susceptible than ‘Cobrançosa’ to olive fruit fly. The effect of nitrogen on the reduction of the incidence of the olive fruit fly was attributed to the delay caused in fruit maturation, which might have desynchronized the attractiveness of the fruits for insects to lay their eggs on their flight curve. In contrast, olive leaf spot and olive anthracnose were not influenced by nitrogen fertilization. As a result, nutrient management in olive groves must balance carefully the requirements of economic rationality with environmental preservation, particularly with regard to the harmful relationship between the use of excessive nitrogen rates and several adverse environmental effects.